A mobile health communication framework for postnatal care in rural Kenya - Mbuthia, Florence (University of the Free State, 2020)
Background: Maternal and neonatal health remains a major challenge in low- and middle-income countries, resulting in the burden of a high rate of maternal and neonatal deaths. Postnatal care is an intervention recommended by the World Health Organization to promote maternal and neonatal health. In spite of this recommendation, uptake of postnatal care in Kenya, as in many other sub-Saharan African countries, has remained low, particularly in rural areas, despite targeted postnatal care services being implemented. Mobile health communication is proposed to promote the uptake of postnatal care; however, no theory-based framework has been developed in this regard to date. This study, therefore, aimed to develop a mobile health communication framework for postnatal care in rural Kenya. Methods: A multi-method research design guided the development of the framework through a multi-phased approach. The first phase systematically reviewed literature to gather the best available evidence on how mobile health communication could strengthen postnatal care in rural areas. The second phase of this study used a visual-based narrative inquiry to explore the experiences of postnatal mothers with health care providers and their views on mobile health communication in a rural area in Kenya. In the final phase, the findings of the preceding phases were used to draft the framework, which was validated by policymakers from the same rural area where data had been gathered. The theoretical underpinning of the study was provided by both the integrative model of behaviour prediction and the theory of change logic model. The integrative model of behaviour prediction was used to identify determinants of postnatal care uptake, while theory of change logic model underpinned the development of the mobile health communication framework by describing what the framework comprised. Results: The findings of the systematic review reveal that one-way messaging is the most common type of mobile health communication that is used in an attempt to strengthen postnatal care in rural areas. Evidence reveals that mobile health communication can be used to improve uptake of postnatal care by influencing the critical determinants that predict behaviour uptake, which are, according to the integrative model of behaviour prediction, intention, skills and environmental factors. The findings also reveal that changing beliefs related to attitudes, perceived norms and self-efficacy can enhance the intention to use postnatal care. Mobile health communication can enhance the skills necessary to use postnatal care, such as breastfeeding, cord care, thermal care, delayed bathing of babies, safer sleep practices, care-seeking and problem-solving. The environmental factors that are considered to hinder uptake of postnatal care in rural areas, and which can be reduced by use of mobile health communication, were inaccessibility, unavailability and unaffordability. The findings of the visual-based narrative inquiry reveal that postnatal mothers had expectations of health care providers, with some expectations being met, and others not. The postnatal mothers reported having positive experiences with their health care providers as a result of the physical and emotional support they received. The positive experiences had various outcomes for both mothers and their children. The findings also reveal that postnatal mothers had expectations of mobile health communication, viewing it as a way in which health education and psychological support in relation to postnatal care could be provided. In addition, they expressed positive attitudes towards mobile health communication – they regarded it as useful for improving access to health care providers, and the availability of and access to the health facility. From the validation exercise, guided by theory of change logic model, a mobile health communication framework for postnatal care in rural Kenya was developed. The model helped to address the problem caused by the absence of a mobile health communication framework in rural areas, by linking postnatal mothers’ needs, the desired results, influential factors and strategies. In addition, the assumptions behind the effectiveness of the framework were highlighted. The framework that was developed integrated the integrative model of behaviour prediction and theory of change logic model. In addition to the models, both users and policymakers’ inputs were incorporated, as was additional literature, which strengthened the framework. Conclusion: In this study, a theory-based mobile health communication framework for postnatal care in rural Kenya was developed on the basis of the best evidence available on mobile health communication, and users’ and the policymakers’ inputs. Given that the mobile health communication framework was developed on the basis of the contextual realities of rural Kenya, its piloting and implementation is recommended, as it is likely to improve the uptake of postnatal care, as well as both maternal and neonatal health, thereby helping to address the high rate of maternal and neonatal mortality, especially in rural settings and in low- and middle-income countries.
Thesis (Ph.D. (Nursing))--University of the Free State, 2020
Keywords: Postnatal care; Rural; Kenya; Logic model; Mobile health communication framework; Postnatal care -- Kenya; Rural health services -- Kenya